Facilitator roles of viruses in enhanced insect resistance to biotic stress - Jagdale, Shounak S.; Joshi, Rakesh S. (Current Opinion in Insect Science, 2019)
Virus-insect interactions are primarily parasitic, yet diverse mutualistic interactions, some of which are symbiogenic, also occur. These viruses can modify insect physiology and behavior so that hosts can gain resistance against various biotic challenges like pathogen and parasites. In the recent past, many insect mutualistic viruses have been reported. Viruses can show symbiogenic interactions with some insects, which have been explored at the molecular level. However, understanding about molecular mechanisms for many of the mutualistic viruses is still enigmatic. Exploration of these interactions and its mechanism can shed light on phenomenon of virus mediated biotic stress resistance in insects.

Discovery of potential multi-target-directed ligands by targeting host-specific SARS-CoV-2 structurally conserved main protease - Joshi, Rakesh S.; Jagdale, Shounak S.; Bansode, Sneha B.; Shankar, S. Shiva; Tellis, Meenakshi B.; Pandya, Vaibhav Kumar; Chugh, Anita; Giri, Ashok P.; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in the current COVID-19 pandemic. Worldwide this disease has infected over 2.5 million individuals with a mortality rate ranging from 5 to 10%. There are several efforts going on in the drug discovery to control the SARS-CoV-2 viral infection. The main protease (M-Pro) plays a critical role in viral replication and maturation, thus can serve as the primary drug target. To understand the structural evolution of M-Pro, we have performed phylogenetic and Sequence Similarity Network analysis, that depicted divergence of Coronaviridae M-Pro in five clusters specific to viral hosts. This clustering was corroborated with the comparison of M-Pro structures. Furthermore, it has been observed that backbone and binding site conformations are conserved despite variation in some of the residues. These attributes can be exploited to repurpose available viral protease inhibitors against SARS-CoV-2 M-Pro. In agreement with this, we performed screening of similar to 7100 molecules including active ingredients present in the Ayurvedic anti-tussive medicines, anti-viral phytochemicals and synthetic anti-virals against SARS-CoV-2 M-Pro as the primary target. We identified several natural molecules like delta-viniferin, myricitrin, taiwanhomoflavone A, lactucopicrin 15-oxalate, nympholide A, afzelin, biorobin, hesperidin and phyllaemblicin B that strongly binds to SARS-CoV-2 M-Pro. Intrestingly, these molecules also showed strong binding with other potential targets of SARS-CoV-2 infection like viral receptor human angiotensin-converting enzyme 2 (hACE-2) and RNA dependent RNA polymerase (RdRp). We anticipate that our approach for identification of multi-target-directed ligand will provide new avenues for drug discovery against SARS-CoV-2 infection. Communicated by Ramaswamy H. Sarma
Keywords: Coronavirus; COVID-19; hACE-2; MPro; multi-target-directed ligand; protease inhibitor; RdRp; SARS-CoV-2 virus